Heavy metals removal by osmotic membrane bioreactor (OMBR) and their effect on sludge properties - Aftab, B; Khan, S; Maqbool, T; Hankins, N (Elsevier, 2016)
Osmotic membrane bioreactor (OMBR) was operated to treat high strength wastewater. Cellulose triacetate (CTA) membrane, having effective membrane area of 0.12 m 2 , in a flat-sheet module configuration was submerged in a bio-tank (working volume 4.5 L). SRT of 20 days and periodic removal of supernatant from settled sludge were maintained to control the salinity level in the bio-tank. Keeping operating conditions constant, the OMBR system was operated in treating 2, 5 and 10 mg/L of Chromium (Cr) and Lead (Pb) metals, respectively of the high strength wastewater. Effect of these metals on membrane fouling, sludge characteristics and treatment performances in term of organic carbon, ammonium-nitrogen and phosphate-phosphorous were investigated. Biomass properties including specific oxygen uptake rate (SOUR), MLSS concentration and capillary suction time (CST) were determined. There was no significant effect of lower concentrations of Cr on sludge properties while 63% of biomass reduction and 42% of biomass activity (SOUR) inhibition were reported for 10 mg/L of Cr. In case of Pb, even its lower concentrations of 2 and 5 mg/L were producing toxic effects on sludge properties i.e., 14.7 and 40% of biomass (MLSS) and 72 and 83% of bioactivity (SOUR) inhibitions were observed for the Pb concentrations, respectively.